Electrical resistivity imaging data for hydrological and soil investigations of virgin Rospuda River peatland (north-eastern Poland) - G. Sinicyn; Ł. Kaczmarek; R. Mieszkowski; S. Mieszkowski; B. Bednarz; K. Kochanek; M. Grygoruk; M. Grodzka-Łukaszewska (Geoscientific Instrumentation, Methods and Data Systems)
The paper deals with the application of the geophysical method for the investigation of the near-subsurface fragile hydrological environments. The study delivers geophysical measurement data performed in the Rospuda wetlands located in north-eastern Poland. The measurements were carried out by means of the electrical resistivity imaging (ERI; also called electrical resistivity tomography, ERT) method, which so far has never been used in this region of the river Rospuda peatland valley. The ERI data were collected in a single survey campaign in November 2022 to account for the wet season. During the campaign, two ERI profiles were measured. The aim of the fieldwork was to provide material for illustration of the arrangement of geological layers creating the wetland. A data repository contains detailed descriptions for each survey site. The study revealed a strong interaction between groundwater, characterized by a thick sandy aquifer, and surface water. In this system, surface present peat constitutes the dominant soil component within the contact zone between groundwater and surface water (with drainage river type). Variations in this relationship will have a direct impact on peat stability and associated hydrological processes. The water-saturated peat electrical resistivity zone (10–40 Ω m) has a thickness ranging from a few to several meters at a maximum (the highest thickness of peats is present near the Rospuda River).